The Relationships Among High School Students’ Scientific Epistemic Beliefs, Conceptions of Learning Physics and Willingness to Perform Scientific Studies in Physics - Kapucu, S (Jurnal Pendidikan Fisika Indonesia, 2021)
The aim of this research is to investigate the relationships among high school students’ scientific epistemic beliefs, conceptions of learning physics and willingness to perform scientific studies in physics. A total number of 526 (male=284, female=242) 9th grade high school students participated in the study. Correlation research was used, and the data were collected with the help of some questionnaires in the form of Likert-scale at just one point in time. To investigate the relationship among the variables Hierarchical Regression Analysis was performed. The results showed that students’ scientific epistemic beliefs in certainty, development, and justification as well as their higher-level conceptions of learning physics – that are, increase of knowledge, applying and understanding and seeing in a new way – are significant and positive predictors of their willingness to perform scientific studies in physics in the final model. This result can imply that increase in students’ such scientific epistemic beliefs and conceptions of learning physics can result in increase in their willingness to perform scientific studies in physics. Moreover, students’ scientific epistemic beliefs and conceptions of learning physics can also be important variables in explaining their intentions or willingness to perform scientific studies in physics. The attempts that can improve both students’ epistemic beliefs and conceptions of learning physics might result in increase in their willingness to perform scientific studies in physics.